Clusters of adverse childhood experiences and unmet need for care coordination. (December 2021) - Anyigbo, Chidiogo; Tarini, Beth A.; Wang, Jichuan; Lanier, Paul
Abstract: Background: The lack of consensus on how to measure ACEs limits our estimation of their impact on health outcomes and understanding of which ACE clusters drive unmet care coordination (CC) needs. Objectives: 1) Identify latent classes of ACEs among a representative group of U.S. children; 2) Examine the association between these classes and unmet needs for CC. Participant and setting: Using the 2016–2017 National Survey of Children's Health, we sampled children ages 0–17 the who had seen >1 healthcare provider within 12 months (n = 38, 758). Methods: We conducted latent class analyses and weighted logistic regression analyses to examine associations between latent classes and unmet need for CC. Results: We identified seven distinct classes: household poverty and parental divorce, household poverty and parental death, household poverty only, household substance abuse and witnessing violence, multiple ACEs, household poverty and child discrimination, and household poverty and household mental illness. Children in the following classes had the greatest odds of unmet need for CC: household poverty only (AOR 2.0; 95% CI, 1.42–2.84), household poverty and household mental illness (AOR 1.67; 95% CI, 1.15–2.44), multiple ACEs (AOR 2.31; 95% CI, 1.53–3.50), and household poverty and child discrimination (AOR 3.55; 95% CI, 1.71–7.37). Conclusions: Children who experienced specific combinations of ACEs, have an increased risk of unmet need for CC, with those experiencing both poverty and discrimination having the highest odds of unmet need for CC. Discrimination widens the gap of unmet CC need for poor children.